Patterns of the aquatic macrophyte cover in Cachoeira Dourada Reservoir (GO-MG) - L. M Bini; L. G Oliveira; D. C Souza; P. Carvalho; M. P. Pinto (Brazilian Journal of Biology)
The relationship between the aquatic macrophyte cover in upper segments of tributaries and this cover in these tributaries but near the reservoir's main body was tested. Sixteen taxa belonging to 12 families of aquatic macrophytes were recorded in Cachoeira Dourada Reservoir. The most frequent species were Eichhornia azurea (frequency of occurrence = 92%; n = 37 sites) and E. crassipes (44%). Upper segments of the tributaries were the main areas colonized by these aquatic macrophytes. The positive relationship between the aquatic macrophyte cover between the upper and lower segments of tributaries indicates the importance of dispersion in the colonization of the arms and the reservoir's main body.